Interactive Mobile Technology in Education: A Systematic Mapping and Bibliometric Analysis - Ghofur, Muhammad Abdul; Prahani, Binar Kurnia; Dawana, Irgy Redityo; Deta, Utama Alan; Anistyasari, Yeni; Kurtuluş, Muhammed Akif (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Interactive mobile technology (IMT) has become an important element in the transformation of modern education, bringing a more open, dynamic, and responsive approach to learning for learners in the digital age. This study aims to explore the impact of using IMT in various educational settings, ranging from primary to tertiary levels. Through bibliometric analysis combined with a systematic review of a number of articles taken from the Scopus database and published over the last five years (2019–2023). This study identified key findings related to the purpose and focus of using IMT in education. The results indicate that these technologies aim to enhance student motivation, engagement, learning quality, critical thinking skills, and creativity, while also improving the accessibility and flexibility of learning. The findings imply that IMT has great potential to bring about positive changes in education, creating a learning environment that is more open, dynamic, and responsive to students’ individual needs. By utilizing this technology effectively, education can deliver learning experiences that are more engaging, relevant, and adaptive to learners’ development. Therefore, it needs to be continuously supported and developed to provide maximum benefits for the learning process and the advancement of education.